Energy Modeling and Net Energy Analysis: Symposium Papers Presented August 21-25, 1978, Colorado Springs, Colorado - Roberts, Fred S.; Waterman, Wendell W.; Institute of Gas Technology (Chicago: The Institute of Gas Technology, 1978)
These papers were presented at a symposium sponsored by the Institute of Gas Technology on "Energy Modeling and Net Energy Analysis" August 21-25, 1978 in Colorado Springs, Colorado. The symposium explored techniques of energy modeling and net energy analysis including those emanating from linear programming, operations research, econometrics, statistical and probabilistic methods and input-output analysis.
Includes bibliographical references.
ne 25/04/2018
Loans
Keywords: Energy Policy; Power Resources